Pseudoxanthoma elasticum presenting in teenage sisters: case report and review of multisystem associations. - Hillan, A.; Convery-Chan, L.; Beer, T.; McKenzie, F.; Ricciardo, B. (European Journal of Pediatric Dermatology, 2021)
Pseudoxanthoma elasticum (PXE) is a rare inherited autosomal recessive disorder of connective tissue that typically presents in the second decade of life. It leads to progressive cutaneous, ocular and cardiovascular manifestations due to calcification. We report two sisters with PXE diagnosed in their teenage years and review the genetics, pathogenesis and multi-system associations. Comprehensive management to mitigate atherosclerotic risk factors and identify emerging sequelae is important to minimise the disease burden.